A pathological complete response to capecitabine plus oxaliplatin regimen combined with tislelizumab in advanced gastric cancer with liver metastases: A case report - Li-Ping Sheng; Yun-Lin Huang; Zhi Wang; Hai-Fang Zhang; Jin-Yan Zhang; Xiao-Yi Lei (Taylor & Francis Group, 2024)
A 66-year-old female patient presenting with dysphagia was diagnosed with stage IV unresectable gastric cancer (cTxN+M1). Multiple liver metastases were identified. The patient subsequently underwent five courses of chemotherapy and immunotherapy, including the capecitabine plus oxaliplatin (XELOX) regimen combined with tislelizumab. After fifth course treatment, it was confirmed that the liver metastases had completely disappeared and the primary tumor had significantly reduced in size. Consequently, a laparoscopy was performed, revealing a retraction-like response in the primary tumor and no obvious metastases in the abdominal cavity. Subsequently, a radical total gastrectomy was carried out through open abdominal surgery. Pathological analysis showed no remaining cancer or lymph node metastases, and the tumor regression was classified as grade 0. The patient has been now receiving additional chemotherapy and immunotherapy to manage any potential residual metastases. This case illustrated the rare and significant impact of combining chemotherapy with tislelizumab, transitioning the treatment approach from palliative to curative. It highlighted the critical role of immunotherapy in managing advanced gastric cancer with liver metastases.